HUBUNGAN SIKAP PEKERJA YANG TERKAIT DENGAN PENERAPAN PROGRAM KESELAMATAN DAN KESEHATAN KERJA (K3) TERHADAP KOMITMEN PEKERJA (STUDI KASUS: PT. ALKONUSA TEKNIK INTI SURABAYA) - Cahyono, Panca Adi; Santosa, Rooslan Edy (Universitas Dr. Soetomo, 2020)
Accidents in the workplace are cases that are no longer a secret. It can happen because of the limied work scurity facilities as well as the weakness of understanding the principle factors that need to be implemented by company. The philosphy of Occupational Health and Safety (OHS) is every worker has the right to the protection of a comfortable work life, Management and employees still do not understand it. They need to understand OHS. This research aimed to examine and analyze the relationship of employee attitudes about implementing OHS programs to the commitment of workers at PT. Alkonusa Teknik Inti. Conducting commitment means that carry out obligations, responsibilities, and promises. Thus, workers must carry out what has been promised to their company. One of them is to comply the company regulations. Data collection technique used questionnaire. The respondents were 30 workers in PT. Alkonusa Teknik Inti. It was purposive sampling. It used validity, reliability, normality and liniearity. The result showed that there was a significant influence to the commitment of workers in the field related to the OHS implementation in PT. Alkonusa Teknik Inti.